Analisis Perbandingan Komparasi Pendidikan Negara Maju untuk Kemajuan Pendidikan Sekolah Dasar di Indonesia - Dwi Ratnawati; Kurnia Dewi Kusumaningrum; Taufik Muhtarom (Jurnal Bintang Pendidikan Indonesia, 2024)
This research discusses the important role of basic education in national development, with the pressure of dissatisfaction between the education systems in developed countries and Indonesia. Drawing insights from superior education models in Finland, Japan and Singapore, this research aims to identify key factors that contribute to the success of these systems and recommendations that can be applied in the Indonesian context. Analysis focuses on curriculum development, teacher quality, technology integration, student-centered learning, and parent/community support. Developed countries prioritize curricula that emphasize 21st century skills, rigorous teacher selection, effective use of technology, student-focused learning, and strong parent/community involvement. By synthesizing the findings of this observational research, this study offers implementable insights for policy makers to improve the basic education system in Indonesia. These recommendations include curriculum reform, teacher training initiatives, technological infrastructure improvements, student-centered pedagogical approaches, and community engagement strategies. Ultimately, this research emphasizes the importance of learning from global best practices while considering Indonesia's unique cultural, social, and economic context to improve basic education nationally.